2013
DOI: 10.1371/journal.pgen.1003400
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolutionary Fate of an Ancestral Primate Endogenous Retrovirus Envelope Gene, the EnvV Syncytin, Captured for a Function in Placentation

Abstract: Syncytins are envelope genes of retroviral origin that have been co-opted for a role in placentation. They promote cell–cell fusion and are involved in the formation of a syncytium layer—the syncytiotrophoblast—at the materno-fetal interface. They were captured independently in eutherian mammals, and knockout mice demonstrated that they are absolutely required for placenta formation and embryo survival. Here we provide evidence that these “necessary” genes acquired “by chance” have a definite lifetime with div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 48 publications
7
94
0
Order By: Relevance
“…Syncytins are proteins derived from the Env gene of retroviruses that have been coopted at least nine times during mammal evolution and are thought to play a role in placentation [68-71]. The placenta is a temporary organ that is formed by the fusion of fetal extraembryonic membrane and the maternal uterine tissue, which facilitates metabolic exchanges through the interface between the mother and the fetus [69].…”
Section: Te Proteins Co-opted As a Results Of Conflict Between Mother mentioning
confidence: 99%
“…Syncytins are proteins derived from the Env gene of retroviruses that have been coopted at least nine times during mammal evolution and are thought to play a role in placentation [68-71]. The placenta is a temporary organ that is formed by the fusion of fetal extraembryonic membrane and the maternal uterine tissue, which facilitates metabolic exchanges through the interface between the mother and the fetus [69].…”
Section: Te Proteins Co-opted As a Results Of Conflict Between Mother mentioning
confidence: 99%
“…We also found that two other endogenous retrovirus-derived genes, ERVV-1 and ERVV-2, also were induced robustly during trophoblast differentiation. The proteins encoded by these genes do not possess fusogenic properties in human trophoblast cells, but their orthologs are capable of promoting fusion in the placentae of more distantly related primates (34). We discovered that the expression of all four of these retrovirus-derived genes in trophoblast cells is downstream of OVOL1 actions.…”
Section: Discussionmentioning
confidence: 97%
“…Although this ERV3 Env is highly expressed in the placenta (26)(27)(28), and has further been shown to be immunosuppressive (12), it is not found in the gorilla (25) and a natural knockout of the gene (via an additional more premature stop codon) in the homozygous state has been identified in 1% of the human population (29), thus excluding any pivotal role in placentation, at least in humans. We had previously proposed that this gene was most probably a "decaying" syncytin, now replaced by syncytin-1 and -2 in higher primates (30). Along these lines, it can be hypothesized that panMars-env2 in marsupials plays a role close to that played by ERV3 in primates before it was functionally replaced by bona fide syncytins and that both the pan-Mars-Env2 and ERV3 proteins are-or have been-involved in the establishment of feto-maternal tolerance, via their common immunosuppressive function.…”
Section: Discussionmentioning
confidence: 99%